Long term follow up of prosthetic valve endocarditis: what characteristics identify patients who were treated successfully with antibiotics alone?. Issue 6 (1st December 1999) - Truninger, K; Jost, C H Attenhofer; Seifert, B; Vogt, P R; Follath, F; Schaffner, A; Jenni, R
Abstract : OBJECTIVE: To identify predictors for the safe use of antibiotic treatment without reoperation in patients with prosthetic valve endocarditis. SETTING: Retrospective study in a tertiary care centre. SUBJECTS AND DESIGN: All 49 episodes of definite prosthetic valve endocarditis (Duke criteria) diagnosed at one institution between 1980 to 1997 were analysed. Ten episodes (20%) were treated with antibiotics only (antibiotic group) and 39 episodes (80%) with combined antibiotic and surgical treatment (surgery group). The analysis included detailed study of hospital records and data on long term follow up which were obtained in all patients by a questionnaire or telephone contact with physician or patient. The length of follow up (mean (SD)) was 41 (32) months in the antibiotic group and 45 (24) months in the surgery group (NS). Long term survival was estimated by the Kaplan–Meier method and compared by the log-rank test. RESULTS: There was no significant difference in age, history of previous endocarditis, number of previous heart operations, vegetations, emboli, type of prosthesis, or percentage of early prosthetic valve endocarditis and positive blood cultures between the two groups. In the antibiotic group, there were more enterococcal (50%; p = 0.005) and in the surgery group more staphylococcal infections (55%; p = 0.048). Annular abscesses (p < 0.0001) and aortoventricular dehiscence (p = 0.02) were more common in the surgery group. No patient in the antibiotic group had heart failure. Long term follow up showed no significant difference between the surgery and antibiotic groups regarding late mortality (14% v 18%) and five year rates of recurrent endocarditis (14% v 16%), event related mortality (14% v 3%, log-rank test), and the need for reoperation (14% v 19%; log-rank test). The only patient with conservatively treated staphylococcal prosthetic valve endocarditis died after reoperation for recurrence. CONCLUSIONS: Haemodynamically stable patients with non-staphylococcal prosthetic valve endocarditis who are carefully supervised can be treated with antibiotics alone without an increased rate of reinfection, reoperation, or death.